1995
DOI: 10.1144/gsjgs.152.5.0861
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic and structural development of the Eastern Pontides, Turkey

Abstract: This paper describes the stratigraphic and structural development of the Eastern Pontides, North Turkey, based on section logging at eight localities, construction of three structural profiles across the mountains, and published literature. The Eastern Pontides comprise a Late Carboniferous to Miocene sequence resting on a basement of Hercynian metamorphics. Late Carboniferous to Scythian sediments are continental clastics interpreted as having been deposited in an extensional half graben. The Middle Triassic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(93 citation statements)
references
References 9 publications
0
93
0
Order By: Relevance
“…Rifting in the Eastern Black Sea probably began in the Late Paleocene with rotation of the Mid-Black Sea High away from the Shatsky Ridge-Caucasus (Russia). Extension and probable oceanic crust emplacement were complete by the Middle Eocene (Robinson et al, 1995a) and the Upper Paleocene to Recent postrift sequence is about 11 km thick.…”
Section: Basin Configuration and Tectonic Settingmentioning
confidence: 97%
“…Rifting in the Eastern Black Sea probably began in the Late Paleocene with rotation of the Mid-Black Sea High away from the Shatsky Ridge-Caucasus (Russia). Extension and probable oceanic crust emplacement were complete by the Middle Eocene (Robinson et al, 1995a) and the Upper Paleocene to Recent postrift sequence is about 11 km thick.…”
Section: Basin Configuration and Tectonic Settingmentioning
confidence: 97%
“…The Şenköy and Berdiga formations are not exposed in the study area. The Upper Cretaceous is characterized by heterogeneous volcanic-sedimentary sequences, variable laterally and vertically due to syn-sedimentary tectonism and arc magmatism (Aydın et al 2008), deposited in a deep-marine environment (Robinson et al 1995). The Upper Cretaceous succession is subdivided into the Çatak, Kızılkaya, Çağlayan and Tonya formations.…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…It formed by north-dipping subduction under the Eurasian continental margin (e.g., Akin 1979;Ş engör and Yilmaz 1981;Okay and Ş ahintürk 1997;Yilmaz et al 1997;Ş engör et al 2003) and the subsequent collision between the Pontides and the Tauride-Anatolide platforms, although the timing of the collision is still controversial (e.g., Robinson et al 1995;Okay and Ş ahintürk 1997;Ş en et al 1998;Ş engör et al 2003). Okay et al (1997) suggested that the collision should date back to late Paleocene to early Eocene, based on field relationships and ages of granitoids.…”
Section: Geological Settingmentioning
confidence: 99%